Translators' strategies for the translation of cultural markers from English into Persian in a literary text - Saberi, Dariush (2015)
This study examined the strategies adopted by six translators in the translation of the cultural markers from English to Persian in The Alchemist, a novel by Paulo Coelho (1992). The study aimed to identify the strategies that the translators have adopted in rendering the cultural markers in the Persian translation of the novel, as well as to analyze to what extent the translators have been observant of the receiving culture. The Descriptive Translation Studies (DTS) theories underlie the study. Data of the study comprise words and compounds extracted from a corpus of six different Persian translations of the English novel based on a database and search tool designed for this purpose. The classification of cultural markers proposed by Newmark (1988) was used as a basis for searching and extracting the cultural markers from the source text. A total number of256,342 words constitute the corpus, from which 39,483 words are in English and 216,845 words are in Persian. The identified translated words and compounds were then analyzed to fmd out how the translators dealt with cultural markers and to determine the strategies adopted by them in translating the sensitive cultural concepts and phenomena. The analysis of the data revealed that certain concepts such as religious names, traditions and rituals are lost in the translated texts, which is attributed to the cultural differences and religious beliefs of the translators and their preferences for the receiving culture. The comparison of the translated data also revealed that Persian translators could have intentionally or unintentionally omitted or changed certain concepts and meanings due to cultural, religious and translatability issues. These changes considered both as translation mistakes and/or translators' intentions to avoid the religious and morality issues in the receiving culture.